THE EFFECT OF BOLDINE ON BODY COMPOSITION AND CARBOHYDRATE METABOLISM IN OBESE MICE - Beatriz Paes Silva; Gustavo Henrique de Souza; Maiara Mikuska Cordeiro; Vinicius Franco de Oliveira; Lívia Bracht; Jurandir Fernando Comar; Rosane Marina Peralta; Adelar Bracht; Anacharis Babeto de Sá-Nakanishi (Arquivos do Mudi, 2023)
Boldine is an alkaloid widely found in boldo leaves. Recent studies have determined itspotential effect on glycemic and lipidemia control. Because of this, the objective of this workwas to evaluate the effect of boldine on body composition and carbohydrate metabolism inobese mice induced by a high-calorie diet. 21-day-old male Swiss mice were divided intocontrol (standard diet), cafeteria (high-calorie diet) and treatment (boldine 20mg/Kg) groups.After 90 days of treatment, the animals were euthanized, the liver was collected, andepididymal, retroperitoneal, mesenteric and brown fats were weighed. Obese animalsincreased body and fat weight, but boldine treatment decreased body weight (17%) andabdominal circumference (15%) and reduced retroperitoneal (66%) and mesenteric (33%) fatweight. Obesity altered the activity of glucokinase and glucose 6-phosphatase in the liver.However, the treatment decreased glucose 6-phosphatase activity (30%) and increasedglucokinase activity (43%). We conclude that boldine can be a potential preparation for themanagement and treating obesity.